Adaptation and Stylistic Treatment of the Text as a Variety of Translation - Behzodova Shaxruza Munisjonovna (International Journal on Human-Computing Studies, 2023)
Depending on the nature of the communicative situation and the purpose of the translation, the translator may have the task not only to translate the text, but also to process it in some way. This article sheds light on adaptation and stylistic treatment of the text as a variety of translation.